The Influence of the Bias on Mechanical Properties of a-C:H CVD Thin Films - Daniel KOTTFER; Marián MARTON; Łukasz KACZMAREK; Mariana Kuffova (Problemy Mechatroniki)
In this study a-C:H (hydrogenated amorphous carbon) thin films were deposited on the 7075 Al alloy without an interlayer using a DC CVD (direct current chemical vapor deposition) method with varied negative substrate bias in order to improve the hardness and Young´s modulus. The highest values of films hardness and Young´s modulus were 25.6±3.5 GPa and 140.3±4.6 GPa, respectively. The measured results show a promising potential of the a-C:H coated 7075 Al alloy for low load (up to 10 N) applications.